Directions in the Development of Commercial Insurance in Poland and Lithuania - Witkowska, Justyna; Lakštutienė, Aušrinė (Comparative Economic Research. Central and Eastern Europe, 2014)
This article analyses trends in the development of the commercial insurance market in Poland and in Lithuania over the last decade. The insurance market changed in the 2002-2011 period. Those changes can be seen in various fields of commercial insurance. Data on the number of insurers, total premiums written, and the trends in claim payments and claim ratios were used to perform a market trend analysis. It should be emphasized that Poland experienced the results of the financial crisis in the insurance market later than Lithuania, which is visible in specific ratios under analysis. In Lithuania, in terms of insurance expenditures, non-life insurance products are definitely more popular, while in Poland life insurance plays the most important role. Poles buy most life insurance from group 1, and Lithuanians from group 3. In the case of non-life insurance, motor vehicle insurance (third-party liability insurance and casco (collision/personal liability insurance)) and property insurance are the leading forms of insurance purchased by both Poles and Lithuanians, as well as other Europeans.